Morphometrical Study of Various Regions of Skin in Non-descript Breed of Pig - C. D. Kachave; C. S. Mamde; S. B. Lambate; N. M. Karad; G. M. Chigure; G. B. Yadav (Indian Journal of Veterinary Anatomy, 2024)
The porcine skin showed similarities to the human skin in terms of general structure, thickness, hair follicles, pigmentation, collagen, lipid etc. The thorough knowledge of skin morphology is essential for dermatologic, cutaneous, pharmacologic and toxicological studies. This experiment was carried out on twelve non-descript pigs, divided into two groups according to their age viz., piglet (up to 2 months of age) and mature pigs (above 6 months of age). The skin samples were collected from various body regions of pig after slaughter and processed for routine histo-morphological studies. The skin of pig was comprised of epidermis, dermis and hypodermis. In the present study, skin thickness was varied according to body regions of pig. The maximum skin thickness was found in snout region in piglet as well as in mature pigs. The dorsal to ventral regions of abdomen showed decreased trend in thickness of skin in both the piglet and mature pigs. The thickness of subcutaneous fat was the lowest in snout region in both the age groups in comparison with other body regions. The subcutaneous fat layer became thinner from dorsal to ventral abdomen regions. The number of hairs per millimeter square of skin was more in dorsal abdomen region. The values for length of hairs were significantly decreased in dorsal to ventral aspect of abdomen. The diameter of hair was highest in dorsal abdomen in piglet and mature pigs. The values for the morphological parameters were higher in the dorsal abdominal region than other regions of body.